Symptoms of Meares-Irlen/Visual Stress Syndrome in subjects diagnosed with Chronic Fatigue Syndrome - Loew, Stephen J.; Marsh, Nigel V.*; Watson, Kenneth (Elsevier, 2014)
Several diagnostic symptoms of the visual-processing deficit Meares-Irlen/Visual Stress Syndrome are remarkably similar to symptom manifestations reported by individuals with chronic fatigue syndrome (CFS). We surveyed the specific incidences of nine widely-recognised symptoms of visual stress (VS) in a group of subjects (n = 20) previously diagnosed with CFS. The presence of each symptom of VS in the CFS group was compared to its respective presence in both an age and sex matched healthy comparison group (n = 46), and an age and sex matched group comprised of individuals (n = 14) diagnosed with VS. Results showed the frequencies of all nine VS symptoms in the CFS-diagnosed group to be significantly higher (p = .032 – p < .0005)than in the comparison group, with only two symptoms being statistically less frequent in the CFS group than in the VS-diagnosed group. The average number of VS symptoms reported by the CFS group was also significantly higher than the comparison group, yet not significantly different from the VS group. Thus, the occurrence of VS symptoms in subjects diagnosed with CFS appears to be far greater than previously reported, which in turn may indicate the interplay of some yet to be identified underlying factor(s) common to both conditions.